Atomkraftens fortalere i Danmark. En samtidshistorisk analyse - Olsen, Niklas; Sylvest, Casper (Historisk Tidsskrift, 2023)
Arguments for Nuclear Power in Denmark: Elements of a Contemporary History Support for nuclear energy in Denmark has been negligible since 1985, when the Danish parliament withdrew the technology from Danish energy planning. In recent years, however, pro-nuclear voices have reappeared. “Nuclear power – no thanks” still reigns in the Danish parliament and the public sphere, but a growing constellation of pro-nuclear views now constitutes a newly resonant vocal minority. In this article, we take stock of the debate by focusing on four ideal-typical positions in Danish pro-nuclear discourse: technologism, ecomodernism, neoliberalism and right-wing populism. Specifically, we ask how we should understand the main arguments being advanced within the last five years: What characterizes these arguments? What is their reach and focus? To what extent are they compatible? Who promotes them? How do they chime with Danish politics and international developments? What are their prospects? And what does the current debate tell us about the role of growth and technology in contemporary Danish history? The article proceeds in three steps. To illuminate the degree of continuity and innovation in the current support for nuclear power, we first present the historical background for the contemporary Danish nuclear debate. Then we map the four prominent positions in the debate, which leads to an overall characterization of support for nuclear power as well as a discussion of the strengths, weaknesses and challenges associated with it in Danish and international contexts . We then reflect on possible explanations for the increased support for nuclear power in recent years. Finally, we conclude that renewed and intensified support for nuclear power in Denmark must be seen in the light of three key features of contemporary Danish history: A high degree of consensus about the grave challenges posed by the climate crisis, increasing familiarity with large investments in non-fossil energy systems, and the declining influence of anti-growth ideologies in Danish politics. Although the practical significance of the support for nuclear power in the coming years is uncertain, the study invites reflection on how we understand and periodize recent Danish history. Central here is the question of how the skepticism towards growth and technology, which emerged in the 1960s and became widespread during the 1970s, is to be interpreted: Is it a general feature or rather a parenthesis in contemporary Danish history?